Pengaruh Lingkungan Kerja, Kepemimpinan, Kompensasi dan Pelatihan Kerja pada Keterikatan Karyawan Hotel Berbintang di Batam - Antony S (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2018)
This research was conducted with the aim to determine the effect of work environment, leadership, compensation and job training variables on employee engagement variables in star-rated hotels in Batam. This research was conducted using survey methods through questionnaires to as many as 380 respondents, namely employees from star-rated hotels in Batam. After being distributed directly to respondents, the questionnaire was collected and managed to get 340 questionnaires that were filled in completely and then the regression data was tested by the author using the SPSS program. From the results of data processing with SPSS it is known that there is a relationship on all variables studied. Based on the results of this study it is known the relationship between variables of work environment, leadership, compensation and job training on employee attachment variables, so that it is expected that the star hotel management can give greater attention to the variables studied above and manage employee attachments as one of the added values ​​and advantages the hotel. Keywords: hotel employee, leadership, working environment, compensation, training, and employee engagement